Official methods of analysis of AOAC International / edited by Dr. George W. Latimer, Jr. - AOAC International (Rockville, MD, USA ; Oxford, UK : AOAC International ; Oxford University Press, 2023)
The most comprehensive collection of over 3,000 validated consensus methods and standards for chemical and microbiological analysis in food, pharmaceuticals, dietary supplements, cosmetics, and environmental matrices. Includes First Action and Final Action methods, SMPRs, appendices on validation and laboratory quality, and maps to international standards.
Includes validated chemical and microbiological methods, appendices, method performance requirements, subject and method indices.
Description based on: 16th ed., 5th revision; title from disc.
Keywords: Agricultural chemistry -- Technique -- Periodicals; Analytical chemistry -- Laboratory manuals; Agricultural chemistry -- Technique; Analytical chemistry; Laboratory manuals; Periodicals; Laboratory manuals